Green economic policy in South Sulawesi - Husain, Fahrisal; Roslianah, Roslianah (Institut Pemerintahan Dalam Negeri Kampus Sulawesi Selatan, 2024)
The Green Economy Index is a measurement process for evaluating Indonesia's achievements and performance transition towards a green economy. Economic transformation policy by adopting the concept of a green economy which is able to synergize economic growth with limited natural resources. A green economy has basic principles, namely creating relatively high economic growth while increasing welfare for society, protecting the quality of the economy and the carrying capacity of the environment. Green Economy Index (GEI) The Indonesian Green Economy Index has 15 indicators covering three pillars, namely economic, social and environmental. In implementing the green economy in South Sulawesi, the policy that will be implemented is managing land change by increasing the capabilities of farmers with agricultural technology to protect against climate change or Climate Smart Agriculture. Environmental services in the form of assistance or incentives to farmers who grow crops while preserving their land or contributing to improving the quality of the environment. Developing natural resources downstream of national policies with technology that does not degrade the environment where local communities depend on nature, and can allocate high added value for farmers.